2015
DOI: 10.1016/j.theriogenology.2015.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Validation of merocyanine 540 staining as a technique for assessing capacitation-related membrane destabilization of fresh dog sperm

Abstract: The aim of this study was to determine whether flow cytometric evaluation of combined merocyanine 540 and Yo-Pro 1 staining (M540-YP) would identify viable dog sperm that had undergone membrane stabilization known to be associated with capacitation in other species, and whether such destabilization is detected earlier than when using the tyrosine phosphorylation and ethidium homodimer stain combination (TP-EH) with epifluorescence microscopy. Semen from nine dogs was collected and incubated in parallel in bica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…Additionally, we also observed a significant increase in tyrosine phosphorylation levels under these conditions both in Whitten's and HTF media. Merocyanine 540 has been previously used in boar (Harrison & Miller, ), dog (Steckler et al, ) and bovine sperm (Aguila et al, ) as an indicator of plasma membrane destabilization, because it binds to the segments of the plasma membrane that are in a higher state of lipid disorder (Langner & Hui, ; Leahy & Gadella, ; Williamson et al, ), indicating that changes in the membrane architecture related to sperm capacitation have initiated. These changes apparently result from cholesterol efflux supporting the addition of cholesterol acceptors such as BSA, which are normally included in the capacitation media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we also observed a significant increase in tyrosine phosphorylation levels under these conditions both in Whitten's and HTF media. Merocyanine 540 has been previously used in boar (Harrison & Miller, ), dog (Steckler et al, ) and bovine sperm (Aguila et al, ) as an indicator of plasma membrane destabilization, because it binds to the segments of the plasma membrane that are in a higher state of lipid disorder (Langner & Hui, ; Leahy & Gadella, ; Williamson et al, ), indicating that changes in the membrane architecture related to sperm capacitation have initiated. These changes apparently result from cholesterol efflux supporting the addition of cholesterol acceptors such as BSA, which are normally included in the capacitation media.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane fluidity, as an early capacitation event, was evaluated using the merocyanine assay (MC540, M6390). MC540 is a hydrophobic dye that stains cell membranes more intensely if their lipid components are in a higher state of disorder (Rathi et al, ) and has been used in dog (Steckler, Stout, Durandt, & Nothling, ), bovine (Aguila, Zambrano, Arias, & Felmer, ) and equine sperm (Ortgies et al, ; Rathi et al, ). Briefly, 5 μl of MC540 (270 μM stock solution) and 2 μl of SYTOX green (20 μM stock solution, Molecular Probes, Eugene, OR, USA) were added to the sperm suspension (2 × 10 6 sperm/ml) and incubated for 30 min at 38.5°C in air and darkness ( n = 3 replicates for each stallion).…”
Section: Methodsmentioning
confidence: 99%
“…Gentle pressure was applied to the cover slide, with the aid of absorbent paper to eliminate the excess liquid. Percentages of cells showing either of the Merocyanine patterns, opaque (low fluidity) or brilliant (high fluidity -high-binding cells), were calculated after counting 200 spermatozoa under fluorescence microscopy (Leica DMLS) using the 100x objective (Steckler et al 2015).…”
Section: Semen Assessmentmentioning
confidence: 99%
“…In addition, Harrison and Miller (2000) observed in pig sperm, activated with bicarbonate, 35 and 52% of MC540 high-binding cells after 9 and 25 min of incubation, respectively. In contrast, Steckler et al (2015) reported 75% of viable dog sperm with destabilized membranes after 2 hr of incubation. On the other hand, Aboagla and Terada (2003) reported that 51% of goat spermatozoa, diluted in a trehalose freezing extender, showed high merocyanine 540 fluorescence after cryopreservation.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, Steckler et al. () reported 75% of viable dog sperm with destabilized membranes after 2 hr of incubation. On the other hand, Aboagla and Terada () reported that 51% of goat spermatozoa, diluted in a trehalose freezing extender, showed high merocyanine 540 fluorescence after cryopreservation.…”
Section: Discussionmentioning
confidence: 92%